Synthetic CaO-based sorbent for high-temperature CO2 capture in sorption-enhanced hydrogen production - Pecharaumporn, Piya; Wongsakulphasatch, Suwimol; Glinrun, Thongchai; Maneedaeng, Atthaphon; Zulkafli, Hassan; Assabumrungrat, Suttichai (Elsevier, 2019)
Calcium precursor and surfactant addition on properties of synthetic alumina-containing CaO-based for CO2 capture and for sorption-enhanced steam methane reforming process (SE-SMR) were investigated. Results showed that the sorbent derived from calcium D-gluconic acid (CG-AN) offered CO2 sorption capacity of 0.38 g CO2/g sorbent, which is greater than 0.17 g CO2/g sorbent of the sorbent derived from calcium nitrate (CN-AN). Addition of CTAB surfactant during synthesis was found to enhance CO2 sorption capacity for CG-AN but not for CN-AN sorbents. Stability tests of the modified sorbents for 10 cycles showed that CG-AN-CTAB provided higher CO2 sorption capacity than CN-AN-CTAB for each corresponding cycle. Incorporation of CG-AN with Ni catalyst (Ni-CG-AN) using wet-mixing technique offered the longest pre-breakthrough period of 60 min for average maximum H2 purity of 88% at 600 °C and a steam/methane molar ratio of 3.